Pengaruh Harga, Kualitas Produk Dan Celebrity Endors Terhadap Keputusan Pembelian Produk Ms Glow - Dina Audiva Adawiyah; Siti Aisyah; Sri Ramadhani (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2022)
This study aims to examine the effect of price, product quality, and celebrity endorsements on purchasing decisions for ms glow products for students at the State Islamic University of North Sumatra, either partially or simultaneously. This study used a quantitative method with data collection using the Likert scale method. The subjects used in this study were active students at the State Islamic University of North Sumatra for the 2022-2023 year, totaling 19,129 people, and taken using the slovin formula with an error rate of 5% totaling 392 students. Data analysis techniques through the IBM SPSS statistics 25 programs. The results of this study indicate that first, the price has a positive and significant effect on purchasing decisions with a significant value of 0.035 <0.05. Second, product quality has a positive and significant effect on purchasing decisions with a significant value of 0.001 <0.05. Third, celebrity endorsements have a positive and significant effect on purchasing decisions with a significant value of 0.001 <0.05. And fourth, simultaneously price, product quality, and celebrity endorsements have a positive and significant effect on purchasing decisions with a significant value <0.05, namely 0.000 <0.05.